Synopsis of the tribe Crotoneae (Euphorbiaceae) in Distrito Federal, Brazil - Muniz Filho, Eduardo; Da Paixão Noronha Pereira, Amanda; Luis Marques Da Silva, Otávio; Rossi Caruzo, Maria Beatriz (Phytotaxa, 2022)
Crotoneae are one of the largest tribes within Euphorbiaceae with great diversity in Brazil, especially the genus Croton with about 300 species in the country. In this contribution, we present a synopsis of Crotoneae in Distrito Federal, located in central Brazil, where the Cerrado is the prevalent phytogeographic domain. The study is based mainly on herbarium collections but we also observed and collected specimens in the field. The only two genera of the tribe that occur in the studied area are Astraea and Croton with 2 and 23 species, respectively. We provide here one synonymization and keys to identify the studied taxa, along with comments on geographic distribution, habitat, morphological relationships and taxonomic notes for each species.